Molecular basis of primary and secondary resistance to imatinib mesylate - Abdul Aziz, Baba (Pusat Pengajian Sains Perubatan, 2012)
Recently, IMATINffi MESYLATE (IM), a selective Tyrosine Kinase inhibitor, is widely used as a frontline therapy for Chronic Myeloid Leukemia (CML). However, development of resistance to IM either primary or secondary, has emerged as a major obstacle in the successful management of CML patients. Development of resistance is a multifunctional phenomenon in patients with CML and is mediated by diversity of mechanisms which could be classified under BCR-ABL dependent or BCR-ABL independent pathways. BCR-ABL dependent mechanisms are most frequently associated with point mutations in tyrosine kinase domain (TKD) of BCR-ABLI and BCR-ABL gene amplification. The types and frequencies of mutation reported in different studies have shown wide variability probably due to different composition of cohorts. But no reports are available from Malaysia. So, this study was undertaken to investigate the frequency and pattern ofBCR-ABL kinase domain mutations utilizing dHPLC, followed by direct sequencing and BCR-ABL gene amplification using FISH on 92 CML patients who showed resistance to IM. Mutations were detected in 20 patients (21.7%). Nine different types of mutations consisting of T315I (n=9), E255K (n=2), M351T (n=2), G250E (n=2), E355G (n=l), Y253H (n=l), G251E (n=l), V289F (n=l) and N368S (n=l) mutation(s) respectively were discovered in these patients. The T315I mutation appeared to be the most predominant type of mutation among Malaysian CML patients. Interestingly, the G25IE and N368S were novel mutations which have not been reported from elsewhere. In the rest 72 IM resistant CML patients, contribution of BCR-ABL gene amplification was investigated, but none of them showed BCR-ABL gene amplification. It is presumed that the mechanisms of resistance in these 72 patients might be due to BCR-ABL independent pathways for which we are probing various candidate mechanisms, utilizing other grants. Different mutations confer different levels of resistance and hence detection as well as characterization of TKD mutations is highly relevant to guide therapy in CML patients. Furthermore we also tried to associate all the factors with the overall survival among the CML patients treated with IM. The CML stage along with the presence of additional chromosomal abnormalities (ACA) showed the most significant association with the overall survival of the patients. Thus, performing conventional cytogenetics is still very crucial in identifYing the presence of ACA and consequently help in predicting the prognosis of the patients.